Shopping Cart Injuries - Donna Davis (EDIS)
“Perhaps you were one of those children who thought of the shopping cart as a mountain for the courageous climber to conquer, or a racecar with you at the wheel. Or you’ve been challenged by one of those children in the grocery store who were not just riding in, but standing in, climbing on, or pushing that shopping cart like it was their own private jungle gym, skateboard, or glider.” This 2-page Family Album Radio transcript was written by Donna Davis and published by the UF Department of Family, Youth and Community Sciences, March 2012.